Media Informasi Kesehatan untuk Pencegahan HIV/AIDS Yang Disukai Generasi Z: Upaya Penurunan Kasus HIV/AIDS di Kalangan Remaja di Indonesia - Nita Ismayati; Agus Rifai; Tika Rahayu (Universitas Wijaya Kusuma Surabaya, 2023)
Purpose Research. A good knowledge and sources of information of HIV/AIDS can decrease the risk of HIV/AIDS transmission in adolescents. Therefore, it is not only the most effective media for adolescents be considered, but also what media is most preferred. This is important because it will have an impact on the frequent use of the media, so the goal of increasing knowledge and behavior change towards the prevention of HIV/AIDS transmission is expected to be achieved. Research Methods. This study was conducted using quantitative method. The population was 242 people with a stratified sampling sample of 71 students from a high school in Jakarta. Respondents' understanding of information shown through videos about HIV/AIDS prevention and information about HIV/AIDS obtained from the KPAN internet site was explored through an online questionnaire using Google form. Analysis Data. Data processing was done with descriptive statistics using the SPSS version 22 application. Results and Discussions Respondents' perceptions showed that HIV/AIDS prevention information obtained from videos was clearer than information obtained from the KPAN website. Respondents preferred videos as a medium that provides information about HIV/AIDS, symptoms, modes of transmission, treatment, prevention, and its impact. Conclusion, Generation Z adolescents prefer video as a medium for HIV/AIDS prevention information. Information obtained from video also influences the respondents' perspective on HIV/AIDS. Video can be recommended as an information media in prevention and reduction of HIV/AIDS for adolescents.Keywords : health information, HIV/AIDS, senior high school student, video, Z generation